2016
DOI: 10.1007/s00394-016-1210-4
|View full text |Cite
|
Sign up to set email alerts
|

Dietary mineral intake and lung cancer risk: the Rotterdam Study

Abstract: ObjectiveLimited data are available on the role of mineral intake in the development of lung cancer (LC). We investigated whether dietary calcium, copper, iron, magnesium, selenium and zinc intake were associated with LC risk.MethodsWe analyzed data from 5435 participants of the Rotterdam Study, a prospective population-based cohort study among subjects aged 55 years and older. At baseline (1990–1993), diet was measured by a validated food frequency questionnaire. LC events were diagnosed on the basis of patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 44 publications
4
35
0
1
Order By: Relevance
“…High heme iron intake showed the strongest association with LC(OR=3.73, 95% CI 2.49-5.58, P Trend <0.001). The risk increase for heme iron intake and LC is compatible with some studies [24,28,30] but differs from other reports [25][26][27]29]. Non-heme iron intake was found to be directly associated with LC (OR=2.08, 95% CI 1.45-2.97, P Trend <0.001) which is in agreement with the study of Zhou et al, [29] who also found an inverse association for heme iron intake and LC.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…High heme iron intake showed the strongest association with LC(OR=3.73, 95% CI 2.49-5.58, P Trend <0.001). The risk increase for heme iron intake and LC is compatible with some studies [24,28,30] but differs from other reports [25][26][27]29]. Non-heme iron intake was found to be directly associated with LC (OR=2.08, 95% CI 1.45-2.97, P Trend <0.001) which is in agreement with the study of Zhou et al, [29] who also found an inverse association for heme iron intake and LC.…”
Section: Discussionsupporting
confidence: 83%
“…On one Table 3 Regarding animal/plant ratio, the putative risk categories correspond to those appearing in the quoted Table. The existing differences between Table and Figure hand, Ward et al, [30] reported a significant risk increase for heme iron in patients with small cell carcinomas. On the other hand, Muka et al, [26] found no risk differences regarding total iron intake and subtypes of LC. In fact, all subtypes tended to be associated in a protective sense.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Die 2017 publizierte Rotterdam-Studie mit 5435 Teilnehmern zeigte keinen Einfluss von Selen (Befragung hinsichtlich der Ernährung) auf das Lungenkrebsrisiko [88].…”
Section: Lungentumorenunclassified
“…To minimize the potential impact of preexisting subclinical malignancy on cognition (i.e., reverse causation), we repeated analyses after excluding the first 2 and 5 years of follow-up. This was performed in sample 1 by excluding the first 2 and 5 years following study entry for persons free of dementia, and the first 2 and 5 years after dementia diagnosis for dementia patients [16, 17]. In sample 2, the first 2 and 5 years after baseline were excluded for both persons with and without MCI.…”
Section: Methodsmentioning
confidence: 99%